2021
DOI: 10.1021/acs.inorgchem.1c01062
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency and -Field Electron Paramagnetic Resonance Spectroscopic Analysis of Metal–Ligand Covalency in a 4f7 Valence Series (Eu2+, Gd3+, and Tb4+)

Abstract: The recent isolation of molecular tetravalent lanthanide complexes has enabled renewed exploration of the effect of oxidation state on the single-ion properties of the lanthanide ions. Despite the isotropic nature of the 8S ground state in a tetravalent terbium complex, [Tb­(NP­(1,2-bis- t Bu-diamidoethane)­(NEt2))4], preliminary X-band electron paramagnetic resonance (EPR) measurements on tetravalent terbium complexes show rich spectra with broad resonances. The complexity of these spectra highlights the limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…While participation of 5d-orbitals in bonding may be sufficient to understand lanthanides in low oxidation states, there is growing evidence that 4f-orbitals are not fully core-like in tetravalent complexes. , ,, X-ray absorption spectroscopy demonstrates that while 5d-orbital participation is similar in Ce III Cl 6 3– and Ce IV Cl 6 2– , oxidation of Ce III to Ce IV enhances 4f participation to a level comparable to 5d involvement . It has also been shown that lanthanide imidophosphorane complexes show increased covalency via 4f-orbital mixing for higher oxidation states with isoelectronic 4f 7 configurations, such as Tb IV more covalent than Eu II , while isovalent lanthanides show decreasing covalency with increasing atomic number, such as Ce IV more covalent than Tb IV . , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While participation of 5d-orbitals in bonding may be sufficient to understand lanthanides in low oxidation states, there is growing evidence that 4f-orbitals are not fully core-like in tetravalent complexes. , ,, X-ray absorption spectroscopy demonstrates that while 5d-orbital participation is similar in Ce III Cl 6 3– and Ce IV Cl 6 2– , oxidation of Ce III to Ce IV enhances 4f participation to a level comparable to 5d involvement . It has also been shown that lanthanide imidophosphorane complexes show increased covalency via 4f-orbital mixing for higher oxidation states with isoelectronic 4f 7 configurations, such as Tb IV more covalent than Eu II , while isovalent lanthanides show decreasing covalency with increasing atomic number, such as Ce IV more covalent than Tb IV . , …”
Section: Results and Discussionmentioning
confidence: 99%
“…20 It has also been shown that lanthanide imidophosphorane complexes show increased covalency via 4f-orbital mixing for higher oxidation states with isoelectronic 4f 7 configurations, such as Tb IV more covalent than Eu II , while isovalent lanthanides show decreasing covalency with increasing atomic number, such as Ce IV more covalent than Tb IV . 23,28 Covalency via overlap of orbitals is known to contribute to bond stabilization. 19 Minasian and co-workers found enhanced participation of 4f-orbitals in complexes of PrO 2 versus TbO 2 , which was attributed to more diffuse 4f-orbitals of Pr.…”
Section: ■ Concepts and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 14 lanthanide elements (Ce–Lu), until recently, the tetravalent oxidation state was readily accessible only for cerium while Pr( iv ), Nd( iv ), Dy( iv ) and Tb( iv ) had only been detected in solid inorganic compounds, double fluorides, oxides, perovskites, 1 or in concentrated aqueous carbonate solutions. 2 Seminal attempts by various groups to isolate molecular complexes of Tb( iv ) and Pr( iv ) were unsuccessful, 3 and only recently Pr( iv ) 4 and Tb( iv ) 5 complexes were finally successfully isolated in organic solvents by taking advantage of the tuning of the +III/+IV oxidation potential by ligand field effects and by a careful choice of the chemical oxidizing agents. These landmark results open a whole new field in lanthanide coordination chemistry and related photonic and magnetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the nature of bonding as ionic versus covalent is a central issue in chemistry. , For f-block elements, there is particular interest in the participation of the lanthanide (Ln) 4f and actinide (An) 5f quasi-valence orbitals in both ionic and covalent bonding. Spectroscopic techniques such as X-ray absorption reveal the characteristics of f-element bonding, often toward understanding and tuning properties. The nature of bonding also determines the thermodynamic properties of molecules, specifically the bond dissociation energy (BDE). For neutral and cationic lanthanide halides, LnX and LnX + , together denoted as LnX 0,+ (X = F, Cl, Br, I), comparable bonding for different lanthanides with a given halide results in similar bond characteristics such as interatomic distances and vibrational frequencies. , In general, diatomics containing related d-block transition metals , or f-block lanthanides exhibit similar properties that indicate common bond character, whereas their BDEs may vary widely. , Among inherently similar LnF, for example, there are large differences among BDEs, such as 486 kJ/mol for YbF versus 623 kJ/mol for LuF .…”
Section: Introductionmentioning
confidence: 99%